Analysis Influence Practices Leadership on the Job Satisfaction of Employees - Said Almaududi; Dwi Putri Budiningtyas; Zuhri Saputra Hutabarat; Heni Pratiwi (Fibonacci: Jurnal Ilmu Ekonomi, Manajemen dan Keuangan, 2026)
This research analyzed the influence of the dimensions of leadership practices on employee job satisfaction. The object of this study is the University of Batanghari Jambi. Research problem refers to the phenomenon of data at the University of Batanghari Jambi, which is indicated by the number of employees in and out within the last 3 years, as well as some of the complaints are often perceived by employees. The problem that arises is: whether the dimensions of leadership practices have an influence on employee job satisfaction. The study used 80 respondents and all respondents were employees of the University of Batanghari Jambi. Multiple Regression Analysis. The results of this study indicate that such practices are leadership dimensions and empower others dimensions encourage both partial and simultaneous positive effects on employee job satisfaction University of Batanghari.